Did the modern state emerge in the 16th century? Holy Roman Empire and the case of Silesia (Discourse of Law and Administration, 2023)
In the construction of modern states, a particularly important role was played by the combinationof supreme, central government, with the dominance of the power of society in the regions.The emergence of the modern state poses many difficulties for legal historians, especially concerningtime, but also space. In the area of the Holy Roman Empire, the multiplicity of states and theirinternal differentiation strengthened the construction of this type of state, an example of which isSilesia, as well as Bavaria, Hesse, or Bohemia. The paper focuses mainly on the administrative factor,but also on the underlying social factor. The construction of a modern administration, sometimesabsolutist, encountering local resistance, is one of the most important factors in the emergence ofmodern states, not only in the 15th century, as the article puts it, but also from the 13th century onwards,as Anglo-Saxon historians would rather boldly have it.
Keywords: Silesia; modern state; political system; Silesian administration; Holy Roman Empire